Can hydrogen-rich water increase nitrite and nitric oxide in patients with central obesity? - Ram B. Singh; Monika Jankajova; Divyank Sharma; Sarthak Sharma; Mohammad Arif Niaz; Oleg Medvedev; Peter Stefanic; Alexander Tarnava; Duried Alwazeer; Emel Uçarer; Najah Hadi; Jagdish Prasad Sharma (Journal of Clinical and Translational Research, 2026)
Background: Inflammation and oxidative stress play important roles in the pathophysiology of cardiovascular diseases. Hydrogen therapy, due to its antioxidant activity, has become a supplementary treatment. Objective: This study aims to investigate whether hydrogen-rich water (HRW) affects nitrite levels, a precursor of nitric oxide. Methods: Of 71 patients who volunteered, only 60 were selected due to the presence of metabolic syndrome and were randomly divided into either an intervention (HRW; n = 30) or placebo group (n = 30) using a computer-generated random number sequence, with participants blinded to the intervention. The participants consumed one tablet three times daily with 250–500 mL of water, and drank the entire solution immediately after complete dissolution on an empty stomach. Results: A significant increase in nitrite levels (8.2% vs. −1.5%, p < 0.001) was observed in the HRW group compared with the control group at the end of the 24-week follow-up, , with a modest decrease in the control group (0.66 ± 0.15 vs. 0.64 ± 0.14, p > 0.05). Thiobarbituric acid-reactive substances, malondialdehyde, and diene conjugate levels, as well as cytokine levels (tumor necrosis factor α and interleukin-6), did not differ significantly at baseline. However, after 12 and 24 weeks, all these biomarkers showed a significant decline in the HRW group, but not in the control group. Conclusion: Treatment with HRW may cause a possible increase in nitrite levels and decrease markers of inflammation and oxidative stress. It is likely that another possible mechanism of benefit from hydrogen therapy may be through an increase in nitrite levels. Relevance for patients: Hydrogen therapy may help protect against cardiovascular diseases.